Implementasi Pembinaan Kerohanian Islam Pondok Pesantren di Rutan Kelas IIB Nganjuk - Ahmad Akbar Beng Lieng (Al-Riwayah : Jurnal Kependidikan, 2025)
Criminal acts are actions that are prohibited by law and subject to sanctions. Perpetrators of criminal acts are often influenced by factors such as need, bad habits, or family environment. The criminal justice process does not only aim to punish, but also rehabilitate perpetrators through guidance in correctional institutions. In Indonesia, the correctional system is based on Pancasila and the 1945 Constitution, emphasizing collaboration between prisoners, supervisors and the community. Law No. 22 of 2022 underlines the importance of coaching to prepare prisoners to return to society. However, overcrowding in detention centers often causes stress and negative behavior. Nganjuk Class IIB Detention Center addresses this issue with an Islamic boarding school-based coaching program aimed at increasing the faith and morals of inmates. This research uses a qualitative method with a case study approach, involving observation, documentation and interviews. The results show that spiritual development programs, such as congregational prayers and recitations, are effective in increasing the spirituality of prisoners. However, challenges such as lack of motivation still exist. Therefore, more interesting coaching strategies are needed to optimally achieve rehabilitation goals. This program also prepares prisoners for reintegration with a stronger faith.